QbD Approach for the Development and Validation of RP-UHPLC Method for Quantitation of Vildagliptin - Sultana, Sharifa; Kumar, Uttom; Hossain, Md Shahadat; Lira, Dilshad Noor; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The present work describes a quality by design (QbD)-based rapid, simple, precise and robust RPUHPLC method for the routine analysis of vildagliptin in bulk drug and in pharmaceutical dosage forms. Chromatographic separation was achieved by a X-bridge C18 column with isocratic elution of mobile phase containing mixture of phosphate buffer (pH 6.8) and acetonitrile in the ratio of 67:33(v/v). The flow rate was 1.0 ml/min and the detection was done at 239 nm with photo-diode array plus (PDA+) detector. The optimization of chromatographic method was carried out by QbD approach using design of experiments (DoE). Two factors utilized for the experimental design of the method were (i) independent variables which comprise percentages of acetonitrile in mobile phase and flow rate and (ii) co-variates which include the retention time, tailing factor and theoretical plates. This design was statistically analyzed by ANOVA, normal plot of residual, box-cox plot for power transform, perturbation, counter plot and 3D response surfaces plots. This was further validated as per the requirements of ICHQ2B guidelines for linearity, LOD, LOQ, accuracy, precision, specificity and robustness. The results showed that proposed method is simple, sensitive and highly robust for routine analysis of vildagliptin. Dhaka Univ. J. Pharm. Sci. 16(1): 107-117, 2017 (June)